2017
DOI: 10.1007/s10495-017-1378-y
|View full text |Cite
|
Sign up to set email alerts
|

Diallyl trisulfide ameliorates myocardial ischemia–reperfusion injury by reducing oxidative stress and endoplasmic reticulum stress-mediated apoptosis in type 1 diabetic rats: role of SIRT1 activation

Abstract: Diallyl trisulfide (DATS) protects against apoptosis during myocardial ischemia-reperfusion (MI/R) injury in diabetic state, although the underlying mechanisms remain poorly defined. Previously, we and others demonstrated that silent information regulator 1 (SIRT1) activation inhibited oxidative stress and endoplasmic reticulum (ER) stress during MI/R injury. We hypothesize that DATS reduces diabetic MI/R injury by activating SIRT1 signaling. Streptozotocin (STZ)-induced type 1 diabetic rats were subjected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 53 publications
1
69
0
Order By: Relevance
“…In endothelial cells, dynamin-related protein 1 (Drp1) triggered mitochondria dysfunction, which was reversed under DATS administration [30]. Silent information regulator l (SIRT1), which acts as the regulator of mitochondrial biogenesis, was significantly enhanced by DATS in myocardial ischemia-reperfusion (MI/R) injury models [31]. Therefore, reviving mitochondrial damage may be another way that DATS can protect cardiac cells from apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In endothelial cells, dynamin-related protein 1 (Drp1) triggered mitochondria dysfunction, which was reversed under DATS administration [30]. Silent information regulator l (SIRT1), which acts as the regulator of mitochondrial biogenesis, was significantly enhanced by DATS in myocardial ischemia-reperfusion (MI/R) injury models [31]. Therefore, reviving mitochondrial damage may be another way that DATS can protect cardiac cells from apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is also referred to as programmed cell death . Resisting apoptosis is one of the most prominent characteristics of neoplasms.…”
Section: Anticancer Mechanisms Of Foxo1mentioning
confidence: 99%
“…Apoptosis is also referred to as programmed cell death. [39][40][41][42][43][44][45][46] Resisting apoptosis is one of the most prominent characteristics of neoplasms. MHY-449, a novel cytotoxic drug, can induce apoptotic cell death in human PC3 prostate cancer cells by downregulating the phosphorylation levels of FOXO1, which is evident in the increased activity of caspase-3, caspase-8 and caspase.…”
Section: Apoptosismentioning
confidence: 99%
“…A number of recently published papers should be highlighted. It was found that the mechanism by which diallyl trisulfide protects against apoptosis during myocardial ischemia-reperfusion injury in diabetic disease, involves activation of silent information regulator-1 (SIRT1) [11]. Another paper related to cardiovascular disease reports on the role of stromal cell-derived factor-1 (SDF-1) in stimulating TNF-mediated apoptosis in cardiac myocytes.…”
Section: The Editors' Choicementioning
confidence: 99%